2017
DOI: 10.1159/000486219
|View full text |Cite
|
Sign up to set email alerts
|

Decreased IFIT2 Expression Promotes Gastric Cancer Progression and Predicts Poor Prognosis of the Patients

Abstract: Background/Aims: The status of interferon (IFN) signaling pathway has been shown to be closely associated with the response of immune checkpoint blockade therapy against advanced human cancers. IFN-induced protein with tetratricopeptide repeats 2 (IFIT2), also known as IFN-stimulated gene 54 (ISG54), is one of the most highly responsive ISGs, which can inhibit the proliferation and migration of cancer cells, and regulate viral replication, resulting in anti-cancer and anti-viral effects. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 20 publications
1
53
0
1
Order By: Relevance
“…Immunohistochemical staining was performed as described in our previous reports [1215]. Briefly, the HCC tissue array block was cut into 4-µm-thick sections, and the sections were dewaxed in xylene and rehydrated in a graded series of alcohols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical staining was performed as described in our previous reports [1215]. Briefly, the HCC tissue array block was cut into 4-µm-thick sections, and the sections were dewaxed in xylene and rehydrated in a graded series of alcohols.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration ability was assessed using a wound scrape assay to examine the role of B7-H6 in regulating the migration ability of HCC cell lines, as described in our previous studies [12, 17, 18]. Briefly, cells from the LV-B7-H6-shRNA and LV-NC groups were maintained in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IFITs are involved in the host immune response and antiviral defense, emerging research studies have shown their involvement in malignant progression (Lai et al, 2008(Lai et al, , 2013Niess et al, 2015;Zhang et al, 2016;Ohsugi et al, 2017;Yang et al, 2017;Zhao et al, 2017;Chen et al, 2018;Lo et al, 2018Lo et al, , 2019Nushtaeva et al, 2018;Shen et al, 2018;Huang et al, 2019). The epithelial-mesenchymal transition (EMT) is a biological mechanism in which epithelial cells convert into a mesenchymal phenotype to acquire increased cell invasion and migration capacity as well as resistance to apoptosis (Kalluri and Weinberg, 2009), which lead to metastasis (Yilmaz and Christofori, 2009).…”
Section: Ifits In Malignant Progressionmentioning
confidence: 99%
“…In contrast, IFIT2 has been shown to have tumor suppressor function in many cancers. Decreased expression of IFIT2 is associated with increased cell proliferation and metastasis and predicts poor clinical outcome in gastric cancer patients (Chen et al, 2018). Downregulation of IFIT2 expression was observed in colorectal cancer (CRC) tissues compared to normal tissues.…”
Section: The Clinical Relevance Of Ifits In Oscc and Other Cancersmentioning
confidence: 99%